Growth and mortality model of Caesio cuning in Karimunjawa National Park, Indonesia - PRANATA CANDRA PERDANA PUTRA; SETYO TRI WAHYUDI; ABU BAKAR SAMBAH; AIDA SARTIMBUL (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Putra PCP, Wahyudi ST, Sambah AB, Sartimbul A. 2024. Growth and mortality model of Caesio cuning in Karimunjawa National Park, Indonesia. Biodiversitas 25: 4215-4222. Global climate change causes an increase in sea surface temperatures and changes in current patterns, which implies the occurrence of marine deoxidation, which has an impact on fish reproduction and growth and coupled with high levels of exploitation, which causes a decrease in fisheries productivity in the Karimunjawa National Park Area, one of which is yellowtail (Caesio cuning (Bloch, 1791)). This study aims to analyze yellowtail growth and mortality model with a biology approach. Samples were collected from as many as 900 individuals during the Northwest and Southeast monsoon season. Data were analyzed using the von Bertalanffy growth model with FAO-ICLARM Stock Assessment Tools II. The results show a significant relationship between the Northwest and Southeast monsoon seasons where growth is negative allometric because b<3 with r2 values ??in each season of 0.85 and 0.89, the growth model obtained (Lt = 389.6[1 - e0.22-(t0+0.37)]) with total mortality of 2.02, where fishing mortality (F) 1.69 and natural mortality (M) 0.33 and produces an exploitation level (E) of 0.84 which indicates that yellowtail has been fully exploited as indicated by the value of E>0.5. The highest recruitment pattern occurs in the Southeast monsoon season (July), amounting to 19.46%. This means that sustainable management is needed to maintain the stock of yellowtail resources in the Karimunjawa National Park Area.